Navigating Uncharted Waters: How Executives Originate High-Quality Ideas for Strategic Responses to Unprecedented Shocks - Barreto, Ilídio (Academy of Management Review, 2025)
How and why do executives originate high-quality ideas for their firms’ responses to major, unprecedented, exogenous shocks? I develop a novel, emergence-based theory of idea origination (TIO) by executives in the context of such shocks. By considering the top management team (TMT) as a complex system, I suggest that executives may arrive at high-quality shock-response ideas due to the (mitigating or reinforcing) workings of dynamic, situation-specific, interrelated constructs located at the individual, dyadic, and team levels of analysis. These constructs are formed and evolve according to an emergence process triggered by the focal shock. In my theorizing, I link dual-process models to idea origination (i.e., the interconnected execution of problem definition and idea generation), identify different modalities of controlled processing and categorizations of dyadic dynamics, and examine the complementary role of autonomous versus dynamics-driven new schema processing. Extant literature on executives’ roles in strategic situations has tended to consider TMTs as monolithic decision-making bodies of individuals carrying enduring, situation-independent, ex ante known characteristics or engaged in stable, uniform interactions. Instead, I conclude that individual executives navigating uncharted waters, such as unprecedented shocks, may actually originate shock-response ideas in much more fickle, multifarious, and shock-specific ways.